PENGARUH GAYA HIDUP, PERSEPSI HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DI PAUL BAKERY RESTAURANT - Muhamad Surya; Yosafat Puji Hastoko (LPPM Universitas Asa Indonesia, 2022)
The purpose of this study was to determine the influence of lifestyle, price perception, and brand image on purchasing decisions, the sample in this study was customers who visited Paul Bakery Restaurant which has a branch in Pacific Place Mall. With a sampling of 100 respondents. The sampling technique uses accidental sampling. The method used in this study is multiple linear regression. This study shows that lifestyle, price perception, brand image have an influence on purchasing decisions both partially and simultaneously.